Development of polymeric anepectic meshes: Auxetic metamaterials with negative thermal expansion - Raminhos, J. S. (2019)
This paper reports the application of additive manufacturing technology to fabricate bi-dimensional lightweight composite meshes capable of demonstrating auxetic properties (negative Poisson's ratio (NPR)) in combination with negative thermal expansion (NTE) behaviour, using as constituent materials polymers that do not exhibit NTE behaviour. To describe the combination of NPR and NTE characteristics, the designation of 'anepectic' is being proposed. Each mesh, obtained from varying either the material combination or the design parameters, was tested on a heated silicone bath to study the effects of the different combinations on the coefficient of thermal expansion (CTE). It was found that all meshes studied demonstrated a successful combination of NPR and NTE behaviours, and it was revealed that there is a possibility to tailor the meshes to activate the NTE behaviour within a chosen range of temperatures. For an extreme case, a Poisson's ratio of-0.056, along with a CTE of-1568 × 10 -6 K -1 has been achieved.